5. CLINICAL AND SUBCLINICAL CHARACTERISTICS OF THYROID NODULES AND SOME RELATED FACTORS IN PATIENTS WITH HASHIMOTO'S THYROIDITIS (Vietnam Journal of Community Medicine, 2023)
Objective: Describe thyroid nodules’ clinical and paraclinical characteristics in patients with chronic Hashimoto’s thyroiditis and some related factors.Subjects and methods: Cross-sectional descriptive study on 115 patients examined at the Endocrinology clinic of Hanoi Medical University Hospital from August 1, 2022, to July 1, 2023, who met the criteria have thyroid nodules (BNTG) detected clinically and/or on thyroid ultrasound, accompanied by the criteria for diagnosis of chronic Hashimoto’s thyroiditis according to the standards of the Japanese Thyroid Association 2022.Results: 87.8% of patients with BNTG on Hashimoto’s thyroiditis were female; the Average age was 45±13 years; 21.7% of patients had a history of Hashimoto’s and the proportion of patients with a history of thyroid nodules was 51.3%; The older were, the larger thyroid gland became; The rate of BNTG in Hashimoto’s thyroiditis classified as TIRADS 4-5 was 51.3%, TIRADS 2-3 was 48.7%, thyroid function on tests is mostly euthyroid.Conclusion: Patients with Hashimoto’s thyroiditis occurs mainly in women with an average age of 45 years. The majority of patients with Hashimoto thyroiditis TIRADS 4 and TIRADS have hypoechoic nuclei and calcified lesions, while the group of patients with TIRADS 2 and TIRADS 3 mainly have mixed nuclei and no calcification. Patients with Hashimoto’s thyroiditis should be examined for cervical cancer early to provide timely diagnosis and treatment.
Keywords: Thyroid nodule; Hashimoto’s thyroiditis.